2014
DOI: 10.1016/j.bone.2013.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy enhances mechanical load-induced solute transport around osteocytes in rat cancellous bone

Abstract: To test if osteoporosis alters mechanical load-induced interstitial fluid flow in bone, this study examined the combined effect of estrogen deficiency and external loading on solute transport around osteocytes. An in vivo tracer, FITC-labeled bovine serum albumin, was injected into anaesthetized ovariectomized and control female Sprague Dawley rats before the right tibia was subjected to a controlled, physiological, non-invasive sinusoidal load to mimic walking. Tracer movement through the lacunar-canalicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…Tibiae were harvested and either put immediately in 10% neutral buffered formalin for 48 hours or frozen at −20 °C. The analysis focused on the cortical and cancellous bone of the proximal tibial metaphysis because our recent studies demonstrated alterations in the lacunar-canalicular porosity surrounding osteocytes in this region [21, 22]. Tibiae from a subset of animals were used for three analyses: a micro-CT analysis to assess cortical microporosity and cancellous microarchitecture, a backscattered electron imaging and nanoindentation analysis to assess mineralization, and a histomorphometry analysis to assess bone turnover, as detailed below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tibiae were harvested and either put immediately in 10% neutral buffered formalin for 48 hours or frozen at −20 °C. The analysis focused on the cortical and cancellous bone of the proximal tibial metaphysis because our recent studies demonstrated alterations in the lacunar-canalicular porosity surrounding osteocytes in this region [21, 22]. Tibiae from a subset of animals were used for three analyses: a micro-CT analysis to assess cortical microporosity and cancellous microarchitecture, a backscattered electron imaging and nanoindentation analysis to assess mineralization, and a histomorphometry analysis to assess bone turnover, as detailed below.…”
Section: Methodsmentioning
confidence: 99%
“…We found that the increase in effective canalicular size measured using a small molecular weight tracer in ovariectomized rats was due to nanostructural matrix-mineral changes at the osteocyte lacunar-canalicular surface. We have also found changes in molecular transport due to mechanical loading in the rat ovariectomy model [22]. …”
Section: Introductionmentioning
confidence: 99%
“…Ciani et al used ovariectomy-induced estrogen-deficient rats to explore the transport of solute around osteocyte. They injected FITC-labeled bovine serum albumin tracer into rats’ tibia during loading and demonstrated that the load-induced solute transport around osteocyte was enhanced in ovariectomized animals (48). Another study reported that androgens inhibits osteogenic responses to mechanical loading in adult male mice (49) demonstrating a close relationship between sex hormones and skeletal mechanobiology.…”
Section: Osteocytes’ Mechano-transductionmentioning
confidence: 99%
“…In another intriguing contribution, Smit, Burger & Huyghe () modelled strain‐induced fluid flow in the BMU and concluded that during compression a fluid influx along the reversal and closing zones and a fluid efflux along the cutting cone occurs. With respect to a potential pathophysiological relevance, altered fluid flow around osteocytes in the lacunar–canalicular network of oestrogen‐deficient mice suggested a role of abnormal fluid flow in osteoporosis (Sharma et al., ; Ciani et al., ). Another type of signal produced by mechanical load in bone is a time‐varying electric field (Otter, McLeod & Rubin, ).…”
Section: Osseous Fluid Flow As An Osteoblast Navigation Landmarkmentioning
confidence: 99%